2018
DOI: 10.1021/acsnano.8b07006
|View full text |Cite
|
Sign up to set email alerts
|

Germanene Epitaxial Growth by Segregation through Ag(111) Thin Films on Ge(111)

Abstract: Large-scale two-dimensional sheets of graphene-like germanium, namely, germanene, have been epitaxially prepared on Ag(111) thin films grown on Ge(111), using a segregation method, differing from molecular beam epitaxy used in previous reports. From the scanning tunneling microscopy (STM) images, the surface is completely covered with an atom-thin layer showing a highly ordered long-range superstructure in wide scale. Two types of protrusions, named hexagon and line, form a (7√7 × 7√7)R19.1° supercell with res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
114
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(119 citation statements)
references
References 33 publications
5
114
0
Order By: Relevance
“…Moreover, the possibility to induce surface metallic states in insulators by means of an intense electric field and turn two dimensional materials into superconductors [525] have opened a new avenue of research. The successful synthesis of a plethora of two-dimensional systems over the last years such as transition metal dichalcogenides [526], layered transition metal oxides [527,528], hexagonal-boron nitride [529], topological insulators [530], 2D-cuprates [531], ferromagnetic 2D systems [532], phosphorene [533], bismuthene [534], silicene, germanene [535,536] and borophene [537] have fuelled the field opening the possibility to investigate doping and induced superconductivity in a large array of different systems.…”
Section: Searches On Other Superconductorsmentioning
confidence: 99%
“…Moreover, the possibility to induce surface metallic states in insulators by means of an intense electric field and turn two dimensional materials into superconductors [525] have opened a new avenue of research. The successful synthesis of a plethora of two-dimensional systems over the last years such as transition metal dichalcogenides [526], layered transition metal oxides [527,528], hexagonal-boron nitride [529], topological insulators [530], 2D-cuprates [531], ferromagnetic 2D systems [532], phosphorene [533], bismuthene [534], silicene, germanene [535,536] and borophene [537] have fuelled the field opening the possibility to investigate doping and induced superconductivity in a large array of different systems.…”
Section: Searches On Other Superconductorsmentioning
confidence: 99%
“…[3] Emerging two-dimensional (2D) monoelemental materials (Xenes) with planar topology have provided more possibilities for the development of novel and robust PTAs (for example,graphene and black phosphorus (BP)). [4] Germanene is ar ecently developed 2D monoelemental material [5] that shows unique advantages over the prototypical 2D Xenes,such as graphene and BP. [4] Germanene is ar ecently developed 2D monoelemental material [5] that shows unique advantages over the prototypical 2D Xenes,such as graphene and BP.…”
mentioning
confidence: 99%
“…[4] Due to their unique properties,including broad absorption, ultrahigh surface-to-volume ratio,t ractable synthesis,e ase of modification, potentially simple metabolism and degradation mechanisms,t heir applications as all-aspect-satisfactory PTAs are promising. [4] Germanene is ar ecently developed 2D monoelemental material [5] that shows unique advantages over the prototypical 2D Xenes,such as graphene and BP. [5b,6] Thewide absorption range of germanium from ultraviolet to NIR region [7] indicates that the synthesized 2D germanene may have ag reat chance to be ar obust PTA.…”
mentioning
confidence: 99%
“…After the pioneering growth of silicene on Ag(111) in 2012, the next, down the column, group 14 monoelemental 2D honeycomb lattices were at the focus. Soon, germanene (2014) and stanene (2015), as well as silicene again, have been realized on diverse surfaces . Moreover, group 13 and 15 analogs such as borophene, phosphorene, antimonene, and bismuthene, have been also synthesized …”
mentioning
confidence: 99%
“…Just recently, our group has demonstrated that a Ag‐Sn surface alloy, instead of a pure Ag(111) template, is involved in the formation of stanene, using such an MBE method . Otherwise, a segregation process is, in a sense, an ideal method to create 2D materials since it is possible to prepare them at relatively high temperatures, resulting in the energetically most stable phases, as in the case of germanene growth . The Ge segregation stems from the temperature dependence of the Ge solubility in the silver‐rich range.…”
mentioning
confidence: 99%